Delegation by Allied Health Professionals to Allied Health Assistants: a mixed methods systematic review. (September 2021) - Sarigiovannis, P.; Jowett, S.; Saunders, B.; Corp, N.; Bishop, A.
Abstract: Background: Delegation by Allied Health Professionals (AHPs) to Allied Health Assistants (AHAs) was introduced in response to various challenges affecting modern health care delivery. However, the clinical and cost-effectiveness of using AHAs is relatively unexplored. Objectives: The aim of this review was to synthesise the available evidence on; firstly, the clinical and cost-effectiveness of interventions delegated by AHPs to AHAs and secondly, AHPs', AHAs' and patients' attitudes and beliefs towards delegation. Data sources: MEDLINE, AMED, CINAHL, Cochrane Library, PsycINFO, PEDro, OTseeker and Web of Science databases were searched from inception until January 2019 without restrictions. Study selection: Primary studies investigating the clinical and cost-effectiveness of any intervention delegated by an AHP, across the spectrum of clinical areas in relation to adult patients, as well as AHPs', AHAs' and patients' attitudes and beliefs about delegation. Data extraction & synthesis: Data were extracted by pairs of reviewers. Thematic analysis and synthesis of descriptive and analytical themes was conducted. Results: Thirteen publications of variable methodological quality were included. Three studies reported quantitative research and ten qualitative research. No study explored the cost-effectiveness. Only one study investigated clinical effectiveness. Training for both AHPs and AHAs and having clear processes in place were identified as important facilitators of delegation. Conclusion and implications of key findings: Delegation is not standardised across AHPs or within each profession. There are clear knowledge gaps regarding the clinical and cost-effectiveness of delegation by AHPs and patients' attitudes and preferences. Further research is needed to facilitate the standardisation of delegation. Systematic Review Registration Number: PROSPERO CRD42019119557